Heat Stress Affects Faecal Microbial and Metabolic Alterations of Rabbits - Bai, Xue; Shi, Yu; Tang, Lipeng; Chen, Li; Fan, Huimei; Wang, Haoding; Wang, Jie; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Microbiology, 2022)
Heat stress can damage the immune system of rabbits, produce oxidative stress and cause many complications. These diseases are characterized by metabolic disorders, but the mechanism is not clear. Therefore, this study aims to reveal the effects of HS on intestinal microorganisms in rabbits and what metabolic pathway disorders are caused by HS. Twelve rabbits were randomly divided into CON (22-24℃) group and HS (30-32℃) group. Both groups were treated for 15 days. Blood and fecal samples were collected on 15d. Serum immune oxidation indexes were measured by commercial ELISA kit, microbiome analysis of rabbit feces by 16S rRNA gene sequencing and non-targeted metabolomics was analyzed by ultra high performance liquid chromatography-mass spectrometry (UHPC MS/MS). The results showed that HS significantly increased the levels of IgG and T-AOC in serum and decreased TNF- α and IL-10. NMDS analysis showed that there was a significant separation of bacterial community composition between HS and CON groups. At the phylum level, the abundance of Firmicutes, Protobacteria and Verrucomicrobiota in HS group was significantly higher, but the abundance of Bacteriodota was lower than that in CON group. At the genus level, V9D2013 group, Haloplasma, Comamonas, Clostridium sensu stricto 1, Ruminiclostridium, Syntrophus Lutispora, Syntrophorhabdus, Paeniclostridium, Clostridium sensu stricto 6, Candidatus Caldatribacterium, Spirochaeta Synergistaceae, Syner-01, [Eubacterium] xylanophilum group, Cellulosilyticum, ADurb.Bin120 and Devosia were significantly were significantly up regulated in HS group. Principal component analysis (PCA) and least squares discriminant analysis (PLS-DA) showed that the metabolism of HS group was significantly up-regulated compared with CON group. HS increased the concentrations of 4-pyridoxic acid, kynurenine, 20-OH-leukotriene B4, sarcogelate and dopamine, and decreased the concentration of pyridoxal. These metabolites mainly affect the metabolic pathways of vitamin B6, tryptophan, neutrophil activation and prolactin in rabbit intestine. It is worth noting that 4-pyridoxic acid, pyridoxal, kynurenine, 20-OH-leukotriene B4, sarcogelate and dopamine are important markers in inflammatory response and oxidative stress.